INTEGRATION OF IBNU SINA'S ISLAMIC EDUCATION THOUGHT IN MUHAMMADIYAH ELEMENTARY SCHOOL - Rofi'ah Rofi'ah; Vivi Indri Asrini (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2023)
Ibn Sina's Islamic educational thinking consists of objectives, curriculum, teaching methods, and teaching competence. According to Ibn Sina, a good pen or teacher is someone who is smart, wise, and exemplary. Ibnu Sina also believes that the output of teaching is for students to become perfect human beings (al-insan kamil) and become people of quality according to their field abilities or the talents of each student. The fact in the field is that there are still teachers who only carry out teaching duties but do not understand the importance of the character of a teacher and the output of the teaching itself. This means that the teacher has not been integrated from the concept of thinking of Ibn Sina's Islamic Education. The purpose of this study was to describe the integration of Ibn Sina's educational thinking at SD Muhammadiyah 1 Wonopeti, so that the scope of this research is: the planning and implementation of learning the integration of Ibn Sina's educational thinking. The research method is field research (fild research) with a descriptive qualitative approach, namely researchers trying to make observations about a phenomenon in a natural state. Data was collected using interviews, observation, and documentation. The results of the study show that the teachers of SD Muhammadiyah 1 Wonopeti have integrated the thinking concept of Ibn Sina's Islamic Education with learning planning which includes objectives, curriculum, methods and concepts of good educators. The implications of this integration are realized by creative and interesting learning through regular and extracurricular and co-curricular teaching and learning activities.